Transversing the Vertical Case Study: A Methodological Approach to Studies of Educational Policy as Practice. (June 2014) - Bartlett, Lesley; Vavrus, Frances
<x xml:space="preserve">Abstract</x> How can scholars trace the global production and circulation of educational policies? The vertical case study incorporates three elements: "vertical" attention across micro‐, meso‐, and macro‐levels, or scales; a "horizontal" comparison of how policies unfold in distinct locations; and a "transversal, " processual analysis of the creative appropriation of educational policies across time. The second half of the article draws upon an ethnographic study of learner‐centered pedagogy in Tanzania to exemplify the vertical case study approach.